Evolving discourses of COVID-19 and implications for medical education: a critical discourse analysis - Tang, Vincent; van Buuren, Asia; Martimianakis, Maria Athina (Tina) (Canadian Medical Education Journal, 2022)
Background: The othering of individuals has been identified as a concern during the COVID-19 pandemic. The purpose of this study was to examine public commentary during early stages of the pandemic for: 1) emerging discourses that highlighted population-level inequities, and 2) the implications these discourses may have for medical education. Methods: Using a critical discourse analysis (CDA) approach, an archive of texts available in the public domain discussing COVID-19 was iteratively created, reviewed, and coded. We used an intersectional framework to analyze how COVID-19 highlighted structural and institutional inequity at the population level. Results: We found 86 representative texts published from March to June 2020. We focused our analysis on implications within Ontario. The two major discourses that emerged were “COVID-19 as Equalizer” and “COVID-19 as Discriminator.” The former emerged in the early stages of the pandemic to mobilize public health recommendations and describe near-universal impacts on the public. The latter followed to highlight new and pre-existing forms of marginalization exacerbated by the pandemic. Conclusions: This study provides a unique perspective on how structural and systemic responses to COVID-19 were shaped through analysis of public discourse, and therefore, has implications for how the COVID-19 pandemic and future pandemics are framed for future medical learners.